Collusion under different pricing schemes. Issue 4 (23rd July 2020) - Gössl, Florian; Rasch, Alexander
Abstract: We analyze collusive outcomes under different pricing schemes in a differentiated product market in which customers have elastic demand. Starting with a situation in which firms can set two‐part tariffs to price discriminate, we consider two policy interventions that ban price discrimination: Firms must set (a) linear prices or (b) fixed fees. We find that collusion at maximum prices becomes harder to sustain under linear prices. By contrast, the analysis shows that the fixed fees policy facilitates collusion at maximum prices. The results have important implications for competition policy.